Writing the Subject of the 21st Century - (:unkn) unknown (My University, 2022)
The questioning of the subject, within the context specific to a society where bonds have loosened in favor of the reign of individuals, remains a subjective and intersubjective issue. This social challenge also concerns social and literary discourse in particular. Hence, some contemporary Francophone novels – from Africa, the Caribbean, and the Indian Ocean – have delved into the theme of the subject-object in the social world, in its relation to oneself and to others. Moreover, by constructing their own idea of the subject of the 21st century, these Francophone narratives offer an aesthetic perspective on the contemporary world. Building on this observation, this essay examines these texts by attempting to discern their approach to the subject, particularly in relation to time, human suffering, and the mystery of the other.
Keywords: African Research